War on terror: reflecting on 20 years of policy, actions, and violence - Buzar, Stipe; Caron, Jean-François (Facing contemporary terrorism, 2024)
"Looking back at the "War on Terror" and its policies, actions, and the violence that followed, this book analyzes the resulting changes in international power structures and the relationship between citizens and their representatives. It defines our shortcomings in opposing this type of violence by demonstrating how the notion of legitimate violence has been broadened. The impact of the "War on Terror" on the public view of Liberalism is explored, as well as its effects on the role of state authorities in our lives. Thus, this book names the lessons we ought to learn from the actions taken against terrorist organizations." --Publisher's description